The curse of the mummy's tomb - Stine, R. L. (New York : Scholastic, 1993)
Lost in an Egyptian pyramid, twelve-year-old Gabe and his cousin Sari find they are not alone.
Includes a preview of Let's get invisible.
"RL4"--P. [4] of cover.
"008-012"--P. [4] of cover.
620
Accelerated Reader AR
Keywords: Mummies -- Juvenile fiction; Pyramids -- Juvenile fiction; Horror fiction